2006
DOI: 10.1016/j.febslet.2006.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage of periodontal tissue in the rat periodontitis model: Effects of a high‐cholesterol diet

Abstract: Studies suggest an association between consumption of a high-cholesterol diet and periodontitis. We addressed the mechanism by which high dietary cholesterol could be detrimental to periodontal health in a rat model. Feeding a high-cholesterol diet augmented the effects of bacterial pathogens and their products (e.g., lipopolysaccharide and proteases) on production of pro-inflammatory cytokines in fibroblasts. High dietary cholesterol also increased mitochondrial 8-hydroxydeoxyguanosine in the periodontal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 20 publications
0
70
0
4
Order By: Relevance
“…Rats were randomly divided into two groups: the periodontal inflammation group received topical application of bacterial pathogens [25 μg/μL Escherichia coli (E. coli) LPS (Sigma Chemical Co., St. Louis, MO, USA) and 2.25 U/μL proteases from Streptomyces griseus (S. griseus) (Sigma Chemical Co.) suspended in pyrogen-free water], and the control group received topically applied pyrogen-free water instead (26). LPS (0.5 μL × 3 times) and proteases (0.5 μL × 3 times) or pyrogen-free water (0.5 μL × 6 times) were introduced into the gingival sulcus of both maxillary first molars daily for four weeks by micropipette, under inhalative anesthesia with an O 2 -isoflurane mixture (26). The tip of the micropipette was placed close to the gingival sulcus and 0.5 μL of the LPS or protease solutions was dropped into the sulcus.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats were randomly divided into two groups: the periodontal inflammation group received topical application of bacterial pathogens [25 μg/μL Escherichia coli (E. coli) LPS (Sigma Chemical Co., St. Louis, MO, USA) and 2.25 U/μL proteases from Streptomyces griseus (S. griseus) (Sigma Chemical Co.) suspended in pyrogen-free water], and the control group received topically applied pyrogen-free water instead (26). LPS (0.5 μL × 3 times) and proteases (0.5 μL × 3 times) or pyrogen-free water (0.5 μL × 6 times) were introduced into the gingival sulcus of both maxillary first molars daily for four weeks by micropipette, under inhalative anesthesia with an O 2 -isoflurane mixture (26). The tip of the micropipette was placed close to the gingival sulcus and 0.5 μL of the LPS or protease solutions was dropped into the sulcus.…”
Section: Animalsmentioning
confidence: 99%
“…Level of 8-OHdG in the isolated mitochondrial DNA was analyzed using an ELISA kit (Japan Institute for the Control of Aging) (26).…”
Section: Measurement Of Tissue 8-ohdgmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Periodontitis is associated with oxidative stress, 10 decreased total antioxidant status, 11 and/or increased lipid peroxidation in gingival crevicular fluid and saliva. 12 Experimentally induced periodontitis provides a valuable model of chronic wounds and alveolar bone loss. Rats treated daily under anesthesia by application of E. coli LPS into the gingival sulcus showed disease as indicated by elongation of rete ridges and onset of apical migration of junctional epithelium at 8 weeks.…”
mentioning
confidence: 99%
“…The interference of different serum lipid subfractions and periodontal infection has been reported by several researchers, 15,16,17 whereas others have reported either no connections 18 or limited connection. 6,19 Till date, a limited number of studies have separately reported the connection between increased OS and hyperlipidemia 11,20 and increased OS and periodontitis. 2,3,4 To the best of our knowledge, only one clinical-based study 11 examined OS parameters in patients with periodontitis with hyperlipidemia, and that study measured parameters systemically in blood serum, not locally in GCF or gingival tissue.…”
Section: Müge Lutfioğlu (A)mentioning
confidence: 99%